English Language Learning for Mild Intellectual Disability Students During Pandemic - Zubaedah Wiji Lestari; N.Dede Koeriah; Nani Nur’aeni (Journal of English Education and Teaching, 2022)
The participation of mild intellectual disability children in school is important because it is a crucial problem of how intellectual disability people can get a job, become independent people, and can live without depending on others. This study intends to analyze the ability of mild intellectual disability students in social interaction and determine their ability to use language in one of the special needs schools in Bandung. This study used a qualitative approach with a case study design. The participants are mild intellectual disability students, English teachers, and school principals in SLB Wartawan in Bandung. The instruments used in this study were observation guidelines, filed notes, and interview guidelines. The data shows that two students categorize “poor”, ten students categorize “fair, and four students categorize “good” in having social interaction. It can be concluded that most students have a fair category in social interaction. Moreover, the data also reveal that from 16 students, four students categorize “poor”, nine students categorize "fair", and three students categorize "good" in their language ability to communicate with others in the classroom. It can be concluded that most mild intellectual disability students have a fair category in their language ability. The result of observation, fieldnotes and interview also show the activity of English language learning for mild intellectual disability students through blended learning during the pandemic.